Study of sofa score for predicting the outcome of patients admitted in ICU at BTGH - Amit C. Kamath; Suresh Harsoor (Al Ameen Medical College, 2020)
Background: Sepsis with Multiple Organ Dysfunction Syndrome (MODS) is a common cause of Intensive Care Unit (ICU) mortality and morbidity. Early initiation of appropriate effective antimicrobial therapy is essential for a favourable outcome in the patient with sepsis. Cultures and serology are available only after 24 to 48 hours. In the crucial hours which determine the prognosis of the patient the physician has to depend on clinical symptoms and demographic data to aid in diagnosis and management. Using scores like SOFA on admission and also in their due course may help in predicting outcome. Objectives: 1) To study correlation between SOFA score and outcome in critically ill patients admitted in ICU. 2) To study and investigate the performance of SOFA score in predicting mortality in ICU admitted patient. 3) To study the discriminatory capacities of an increase in SOFA score by 2 or more for outcome in patients who are critically ill patients admitted in ICU. Materials and Methods: The study was carried out in the period of November 2017 to April 2019 and 75 patients were included in the study. The detailed history, clinical examination and all the relevant laboratory investigations were done. In the present study, the conditions were defined according to standard practice and based on relevant literature. All the patients of sepsis admitted to ICU/ emergency ward were prognosticated on the basis of SOFA score. We have analyzed various profiles between two groups; survivor group which include the patients who are successfully discharged after recovery and non-survivor group which include the patients who died. Results: The clinical profile of 75 patients with sepsis with MODS was studied. There were 42 males and 33 females in this cohort. In this study, 25 patients died and 50 patients survived with mortality rate of 33.33%. SOFA score has been validated extensively for prognosticfication. In this study, extensive study of SOFA score was done from day 1 to the last day. The SOFA score on day 1 was high among non survivors and survivors which was statistically significant (9.40 v/s 7.72, p=0.023). However, the most significant difference was observed on all days. The SOFA score was very high among non-survivors as compared to survivors which was statistically very significant (13.11 v/s 1.84, p<0.001). Conclusion: Serial measurement of SOFA score during first week is a very useful tool in predicting the outcome. The trend of SOFA score was progressively declining in survivors while non-survivors had a stable higher score during the first week.